Europeanization and European Integration : From Incremental to Structural Change - Coman, Ramona; Kostera, Thomas; Tomini, Luca; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
After two decades of research into the impact of the EU on domestic politics and policies, this book explores the relationship between Europeanization and EU integration. It argues that Europeanization should be considered as a stage in the development of EU integration as well as questioning the notion of incremental Europeanization.
Keywords: Political science; Political theory; Democracy; European Union; Globalization; Political sociology